2014
DOI: 10.1186/1476-511x-13-142
|View full text |Cite
|
Sign up to set email alerts
|

Combination of unsaturated fatty acids and ionizing radiation on human glioma cells: cellular, biochemical and gene expression analysis

Abstract: BackgroundBased on previous observations a potential resort in the therapy of the particularly radioresistant glioma would be its treatment with unsaturated fatty acids (UFAs) combined with irradiation.MethodsWe evaluated the effect of different UFAs (arachidonic acid (AA), docosahexaenoic acid (DHA), gamma-linolenic acid (GLA), eicosapentaenoic acid (EPA) and oleic acid (OA)) on human U87 MG glioma cell line by classical biochemical end-point assays, impedance-based, real-time cellular and holographic microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 64 publications
1
36
0
Order By: Relevance
“…It has been revealed that miRNAs can mediate the inhibition effects of radiation on cancer progression. We then checked the expression of miR‐1, miR‐146a, miR‐155‐5p, miR‐181, miR‐21, miR‐221, miR‐34a, and miR‐760, which were involved in the therapeutic effect of radiation , in NSCLC cells treated with 2 Gy radiation. Our data showed that radiation can significantly increase the expression of miR‐155‐5p and miR‐760, while decrease the expression of miR‐221, in A549 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been revealed that miRNAs can mediate the inhibition effects of radiation on cancer progression. We then checked the expression of miR‐1, miR‐146a, miR‐155‐5p, miR‐181, miR‐21, miR‐221, miR‐34a, and miR‐760, which were involved in the therapeutic effect of radiation , in NSCLC cells treated with 2 Gy radiation. Our data showed that radiation can significantly increase the expression of miR‐155‐5p and miR‐760, while decrease the expression of miR‐221, in A549 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RT‐CES protocol was performed as described previously with slight modifications. RT‐CES 96‐well E‐plate (Roche, Budapest, Hungary) was coated with gelatin solution (0.2% in PBS) for 20 min at 37°C, then gelatin was washed twice with PBS solution.…”
Section: Methodsmentioning
confidence: 99%
“…There is increasing literature support that the benefits of n-3 PUFA consumption are mediated by miRNA regulation; Recchiuti et al (35) demonstrated that the anti-inflammatory role of resolvin, n-3 PUFAderived eicosanoids, is associated with specific miRNA target genes involved in resolution of acute inflammation (e.g. miR-21, miR-146b, miR-208a, miR-203, miR-142, miR-302d, and miR-219); Antal et al (36) showed that miR-146 and miR-181a are induced by docosahexaenoic acid in glioma cells increasing sensitivity of radiation therapy. More recently, Ortega et al (37) suggested that dietary PUFA consumption is linked with changes in plasma circulatory miRNA profiles.…”
Section: Discussionmentioning
confidence: 99%